Engineering device to empower lifeguards in public swimming pools - Foo, Wei Han (Nanyang Technological University, 2022)
Swimming is one of the most popular recreational activities in Singapore. As with any activity, it comes with its risk which is drowning. There are generally two types of swimming pools, private and public pools. In private pools, lifeguards are not required, adults are responsible for their own safety and children are to be supervised by their parents or an adult to ensure safety. This led to the majority of drowning cases happening in private pools. Furthermore, designs of private swimming pools differ based on each locations constrain. As for public pools, designs of swimming pools are roughly of the same design and lifeguards are mandatory. Thus, the drowning cases are significantly lower. However, in Singapore, lifeguards face a shortage in manpower. From the market research done, most of the devices available for drowning prevention are either for personal use, for use when the swimming pool is not in operation or traditional tools such as the torpedo tube and rope. The only new solution that directly impacts lifeguards is in the form of a surveillance device leaving no new solution that impacts lifeguards in terms of rescue operations. As a final year engineering student that works part time as a Lifeguard at Hydro Dash, the author aspires to combine his lifesaving and engineering knowledge to empower his fellow lifeguards by producing a device. This device should aid in terms of rescue operations to potentially decrease the chances of deaths by drowning and allow swimmers to swim safely even when there is a lack of lifeguards. If successful, private pools can then be investigated to implement the device base on their individual layouts to allow the supervising adults to conduct their own rescue with a safer approach. The process to formulate the device was firstly by literature review to better understand the drowning situation in Singapore and the potential reasons that caused drownings in swimming pools. As swimming pools are considered aquatic facilities, the SS556: 2010 which is the code of practice for the building of aquatic facilities was investigated to determine the constrains that the author might face when designing the device. For a more holistic approach to tackle this project, the SS556: 2010 was also investigated to create new preventive solutions that can be included to update the 12-year-old document. After which, the conceptualisation of the device was done by implementing what the author had learnt in Engineering Design (MA4001) and by working with the author’s colleagues from Hydro Dash and organisations such as Nanyang Technological University Lifeguards Corps and Nanyang Technological University Sports and Recreational Centre to formulate the interpreted needs for the device leading up to the conceptualisation of the Anti-drowning Platform System. The Anti-drowning Platform System is a platform that transforms a competition pool that is 1.2m to 1.8m deep into a pool that is 1.2m deep throughout. For the concept to be a viable solution, it needs to be fast, able to withstand impact and shock and be able to bear the load of the swimmers that will be standing on it. To ensure that the concept can withstand the loads due to its application, Machine Element Design (MA3001) is utilised to calculate the dimensions needed to withstand the loads and to select the parts needed. With the conceptualisation and calculation done, Engineering Graphics (MA2005) is used to model the device via Solid Works and then simulation is done to verify that the design can withstand its calculated load. Therefore, in this report, it details the thought process and steps taken by the author from ideation to creation for the Anti-Drowning Platform System that works when there is a time of need and is reliable.